Peritoneal flap for lymphocele prophylaxis following robotic-assisted radical prostatectomy with lymph node dissection: the randomised controlled phase 3 PELYCAN trial - Neuberger, Manuel; Kowalewski, Karl-Friedrich; Simon, Valentin; Hardenberg, Jost von; Siegel, Fabian; Wessels, Frederik; Worst, Thomas; Michel, Maurice Stephan; Westhoff, Niklas Christian; Kriegmair, Maximilian; Honeck, Patrick; Nuhn, Philipp (European urology oncology, 2024)
Background - Symptomatic lymphoceles (SLCs) after transperitoneal robotic-assisted radical prostatectomy with pelvic lymph node dissection (PLND) are common. Evidence from randomised controlled trials (RCTs) on the impact of peritoneal flaps (PFs) on lymphocele (LC) reduction is inconclusive. - Objective - To show that addition of PFs leads to a reduction of postoperative SLCs. - Design, setting, and participants - An investigator-initiated, prospective, parallel, double-blinded, adaptive, phase 3 RCT was conducted. Recruitment took place from September 2019 until December 2021; 6-month written survey-based follow-up was recorded. Stratification was carried out according to potential LC risk factors (extended PLND, diabetes mellitus, and anticoagulation) and surgeons; 1:1 block randomisation was used. Surgeons were informed about allocation after completion of the last surgical step. - Intervention - To create PFs, the ventral peritoneum was incised bilaterally and fixated to the pelvic floor. - Outcome measurements and statistical analysis - The primary endpoint was SLCs. Secondary endpoints included asymptomatic lymphoceles (ALCs), perioperative parameters, and postoperative complications. - Results and limitations - In total, 860 men were screened and 551 randomised. Significant reductions of SLCs (from 9.1% to 3.7%, p = 0.005) and ALCs (27.2% to 10.3%, p < 0.001) over the follow-up period of 6 mo were observed in the intention-to-treat analysis. Operating time was 11 min longer (p < 0.001) in the intervention group; no significant differences in amount (80 vs 103, p = 0.879) and severity (p = 0.182) of postoperative complications (excluding LCs) were observed. The survey-based follow-up might be a limitation. - Conclusions - This is the largest RCT evaluating PF creation for LC prevention and met its primary endpoint, the reduction of SLCs. The results were consistent among all subgroup analyses including ALCs. Owing to the subsequent reduction of burden for patients and the healthcare system, establishing PFs should become the new standard of care. - Patient summary - A new technique—creation of bilateral peritoneal flaps—was added to the standard procedure of robotic-assisted prostatectomy for lymph node removal. It was safe and decreased lymphocele development, a common postoperative complication and morbidity. Hence, it should become a standard procedure.